Determinant of Cocoa Export in Indonesia - Medha Wardhany; Fauzul Adzim (Economics Development Analysis Journal, 2018)
International Trade is one of the activities that plays an important role for the economy. Indonesia is one of the countries whose depends on exports. One of the agricultural commodities that become the leading commodity is cocoa. Although it is a main flag export commodity, cocoa farming still has many challenges. The export volume of cocoa beans in the period 1987-2016 increase slightly, but in the last six years the export tend to decrease. The purpose of this study is to analyze the factors that affect the export of cocoa beans. The analytical method used is Multiple Linear Regression with the ordinary least squares rank method (OLS). The results showed that the variables of production have a positive and significant effect with coefficient value of 0.642607. Domestic cocoa price does not affect the export volume of cocoa beans. The international cocoa price variable has a negative and significant effect on export volume of Indonesian cocoa beans with coefficient value of -7,073793. The rupiah exchange rate variable to US Dollar has a positive and significant effect on the export volume of Indonesian cocoa beans with coefficient value of 15.22362. While simultaneously, production variables, domestic cocoa prices, international cocoa prices, and Rupiah exchange rate against US Dollar together affect the export volume of Indonesian cocoa beans.